The role of stoichiometry in superconducting Nb1−βSnβ: electronic and vibrational properties from ab initio calculations. Issue 48 (24th November 2016) - Gala, F.; De Marzi, G.; Muzzi, L.; Zollo, G.
Abstract : Using first principles calculations the electronic, vibrational and superconducting properties of Nb3 Sn compounds with different stoichiometry ratios in the A15 phase have been studied. Abstract : Using first principles calculations based on density functional theory, the electronic, vibrational and superconducting properties of compounds with different stoichiometry ratios in the A15 phase have been studied. To this purpose, the λ mass enhancement parameter, which determines the superconducting critical temperature through the Allen–Dynes modification of the McMillan formula, has been explicitly calculated in the context of the density functional perturbation theory that allows the calculation of the matrix elements of the electron–phonon interactions at different compositions related to the Sn content. Our results provide a better understanding of the inhomogeneous composition of one of the most widely employed low-temperature superconductors, evidencing the electronic properties and the phonon modes that are responsible for the critical temperature degradation as the Sn concentration is varied.